Science Diplomacy as a tool of international politics: the power of ‘soft power’ - Domingues, Amanda; Ribeiro Neto, Paulo Henrique (Faculdade de Filosofia e Ciências, 2018)
Science and Technology (S&T) have historically been used by countries as tools of hard power, especially in military and economic contexts. Contrary to a strategy that uses S&T as a hard power tool, Science Diplomacy (SD) is an alternative form of using S&T in bilateral and multilateral interactions; one in which soft power predominates. Relying on examples of the foreign relations of the United States - one of the most developed countries in terms of S&T and SD - this article shows how SD has unified countries and has been employed as a strategy that assists diplomats in interpreting technical knowledge, supports scientists in negotiating multilateral projects, and, most importantly, promotes alliances between countries. The paper is divided in three main sections: in the first part, we present a brief summary of the intellectual history of the concept of SD, introducing and defining it and we discuss why countries invest in it. In the second part, we analyze to what extent S&T played a central role in re-establishing bilateral relations or in promoting more peaceful negotiations between the U.S. and Cuba, North Korea, Russia, and selected Muslim countries. In the third section, we offer our concluding remarks. Key-words: Science Diplomacy; International Cooperation; Science and Technology.     Recebido em: maio/2017 Aprovado em: janeiro/2018